Investigation of Causes and Risk Factors for Gastrointestinal Bleeding (GIB) in Patients Referring to Shahid Mostafa Khomeini Hospital, Ilam City, from 2014 to 2019 - Hossein Seidkhani; Azadeh Barkhordarian Abadeh; Masoud Mami (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2023)
Introduction: Gastrointestinal bleeding (GIB) is one of the most important diseases in internal medicine, which can occur due to bleeding in any of the gastrointestinal organs. The best diagnostic method for identifying the source of bleeding in patients is endoscopy and colonoscopy. Therefore, this study was conducted to determine the causes and the most common risk factors for GIB in patients referring to Shahid Mustafa Khomeini Hospital in Ilam. Material & Methods: In this retrospective analytical study, all patients with clear gastrointestinal bleeding symptoms, including melena, hematemesis, hematochezia, and passing clots, who referred to Shahid Mustafa Khomeini Hospital in Ilam from 2014 to 2019, were evaluated. The demographic information of the patients, their medical history, and the description of the medications they were taking, which were recorded in their medical records, were entered into the questionnaire form. Data analysis was performed using descriptive and inferential statistical methods. Findings: In this study, 650 patients with an average age of 57.24 years, ranging from 19 to 99 years, were included. The majority of patients were in the older age group (above 60 years) and were male. The most common complaint among patients was hematemesis (41.4%), while anemia was the least common complaint (1.8%). The most common causes of gastrointestinal bleeding in both genders were peptic ulcer, gastric mass, and esophageal varices. There was a significant correlation between age and gastrointestinal bleeding symptoms (p < 0.05). Gastrointestinal bleeding symptoms, including hematemesis, melena, and rectorrhagia, were more common in men and in smokers. Alcohol consumption also had an impact on the occurrence of gastrointestinal bleeding with hematemesis, melena, and rectorrhagia. Discussion & Conclusion: Endoscopy and colonoscopy are the best diagnostic methods for patients with gastrointestinal bleeding. Therefore, this study was conducted to determine the causes and the most common risk factors for GIB in patients referring to Shahid Mustafa Khomeini Hospital in Ilam from 2014 to 2019. The findings of this study can help improve the diagnosis and management of gastrointestinal bleeding in these patients.